PENGAPENGARUH TUNJANGAN PROFESI TERHADAP KINERJA YANG DIMEDIASI OLEH KEPUASAN GURUANGAN PROFESI TERHADAP KINERJA YANG DIMEDIASI OLEH KEPUASAN GURU - Nurmasi Nurmasi; Buyung Sarita; Aidin Hudani Awasinombu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This research intends to empirically examine and analyze the effect of job aids on the performance mediated by the satisfaction of elementary school teachers in Wangi-Wangi and Wangi-Wangi Selatan. This research is explanatory which intends to explain the position of the researched variables as well as the correlation and the effect among one variable and another. The result shows that: (1) Job aids has positive and significant effects on teachers satisfaction in Elementary Schools in Wangi-Wangi and Wangi-Wangi Selatan. (2) Job aids has positive and significant effects on teachers performance in Elementary Schools in Wangi-Wangi and Wangi-Wangi Selatan. (3) Satisfaction has positive and significant effects on teachers performance in Elementary Schools in Wangi-Wangi and Wangi-Wangi Selatan. (4) Satisfaction can mediate the effect of job aids on teachers performance in Elementary Schools in Wangi-Wangi and Wangi-Wangi Selatan.